Effect of Habitat Diversity on Population Development of the Amazon River Prawn - Santos, Michelle R. [UNESP]; Rodrigues, Caio G. [UNESP]; Valenti, Wagner C. [UNESP] (National Shellfisheries Association, 2016)
The aim of this study was to determine if the Amazon river prawn [Macrobrachium amazonicum (Heller, 1862)] population structure is affected by habitat heterogeneity. An experiment was conducted in mesocosms to emulate conditions from a natural aquatic environment. Twelve rectangular earthen ponds of ∼100 m2 each were used as mesocosms. Each mesocosm was stocked with 22 juveniles/m2 of Amazon river prawn in three different treatments: GB: mesocosm with substrate made of geotextile blanket, BB: mesocosm with substrate made from bamboo, and WS: mesocosm without substrate. The prawns were sampled monthly for 5 mo to analyze the male morphotypes, incidence of eggs in female pleopods, ovarian stage, body mass, and sex ratio. Both geotextile blanket (GB) and bamboo (BB) substrates increased frequency of the Cinnamon Claw morphotype, accelerated the appearance of Green Claw 1 and 2 morphotypes, and decreased the frequency of the Translucent Claw morphotype at the 5th mo. The substrates also increased the size of both sexes of prawn and increased the frequency of ovigerous females and females with ovarian stages IV and V. The effect was more pronounced with the presence of the GB, which imitates natural substrates with large and flat surfaces such as leaves and stones. Sex ratio did not differ significantly between treatments. Data showed that the presence and the type of substrate in the environment can play an important role in M. amazonicum population development, supporting the hypothesis that the population structure of M. amazonicum depends on the habitat characteristics.
Keywords: habitat heterogeneity; macrobenthos; morphotypes; substrates